Distribution of particles, small molecules and polymeric formulation excipients in the suprachoroidal space after microneedle injection. (December 2016) - Chiang, Bryce; Venugopal, Nitin; Edelhauser, Henry F.; Prausnitz, Mark R.
Abstract: The purpose of this work was to determine the effect of injection volume, formulation composition, and time on circumferential spread of particles, small molecules, and polymeric formulation excipients in the suprachoroidal space (SCS) after microneedle injection into New Zealand White rabbit eyes ex vivo and in vivo . Microneedle injections of 25–150 μL Hank's Balanced Salt Solution (HBSS) containing 0.2 μm red-fluorescent particles and a model small molecule (fluorescein) were performed in rabbit eyes ex vivo, and visualized via flat mount. Particles with diameters of 0.02–2 μm were co-injected into SCS in vivo with fluorescein or a polymeric formulation excipient: fluorescein isothiocyanate (FITC)-labeled Discovisc or FITC-labeled carboxymethyl cellulose (CMC). Fluorescent fundus images were acquired over time to determine area of particle, fluorescein, and polymeric formulation excipient spread, as well as their co-localization. We found that fluorescein covered a significantly larger area than co-injected particles when suspended in HBSS, and that this difference was present from 3 min post-injection onwards. We further showed that there was no difference in initial area covered by FITC-Discovisc and particles; the transport time (i.e., the time until the FITC-Discovisc and particle area began dissociating) was 2 d. There was also no difference in initial area covered by FITC-CMC and particles; the transport time in FITC-CMC was 4 d. We also found that particle size (20 nm–2 μm) had no effect on spreading area when delivered in HBSS or Discovisc. We conclude that (i) the area of particle spread in SCS during injection generally increased with increasing injection volume, was unaffected by particle size, and was significantly less than the area of fluorescein spread, (ii) particles suspended in low-viscosity HBSS formulation were entrapped in the SCS after injection, whereas fluorescein was not and (iii) particles co-injected with viscous polymeric formulation excipients co-localized near the site of injection in the SCS, continued to co-localize while spreading over larger areas for 2–4 days, and then no longer co-localized as the polymeric formulation excipients were cleared within 1–3 weeks and the particles remained largely in place. These data suggest that particles encounter greater barriers to flow in SCS compared to molecules and that co-localization of particles and polymeric formulation excipients allows spreading over larger areas of the SCS until the particles and excipients dissociate. Highlights: Studied spread in suprachoroidal space (SCS) post microneedle injection in rabbit eye. Particles in saline were entrapped in the SCS after injection; fluorescein was not. Particles injected with polymers co-localized while spreading in SCS for 2–4 days. After 1–3 weeks, polymers were cleared from SCS, but particles remained in place. Co-localization with polymer allowed spreading of particles in SCS.